Synthesis of Aryl(benzyl)-(Z)-N-[2-Amino-1,2-dicyanovinyl]-formamidines - Yahyazadeh, Asieh; Pourrostam, Babak (Asian Journal of Chemistry, 2016)
Starting from readily available ethyl(Z)-N-[2-amino-1,2-dicyanovinyl]-formimidate 1, the N-aryl (or benzyl)-N´-(2-amino-1,2-dicyanovinyl)formamidines 2 can be prepared in good yields by reaction with aromatic amines at room temperature in the presence of a catalytic amount of aniline hydrochloride.